The role of endnote in the process of reference writing - Jahani, A. (2010)
The aim of this study was to investigate the role of Endnote in the process of reference writing for a thesis. Endnote is software that everybody wants to write references in his research or thesis can use it. Since, there are many resources available because of advances in technology; it seems that Endnote will be used in the future by many researchers. Therefore, learning how to use this software can be a great help to all the researchers. But, the most important question is that: is there any significant relationship between using of Endnote and having better references in thesis? Therefore, two groups of Master students were selected as the subjects of the present study as control and experimental groups. They had to do a research before their graduation .First of all, the student as experimental group had instruction in order to get familiar with Endnote software and another group (control group) did not receive any instruction.It must be mentioned that the site of this study was Iran, Bojnord and the samples were selected the master students who were studying in Azad University. And the instruments used in this study for data collection were questionnaire and interview. The result showed that there were not any significant differences between control and experimental groups and consequently, the researcher has concluded that the using of Endnote software cannot be effective enough to make any differences between two groups.